Rational emotive behavioural counselling in action - Dryden, Windy; Neenan, Michael; Sage eBooks (London : SAGE, 2004)
Windy Dryden introduces the key elements of rational emotive behavioural theory and practice, and outlines the counselling sequence when working through a particular problem with a client.
Previous ed.: 1999.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Rational emotive behavior therapy; Electronic books